SEEDLING PRODUCTION OF Eucalyptus grandis ON ALTERNATIVE ORGANIC SUBSTRATES - Silva, Rodrigo Ferreira da (2014)
http://dx.doi.org/10.5902/1980509815745Studies regarding the disposal of urban and agro-industries waste have become essential for the possibility of their use in forest seedling production and the environmental impact that would be caused by improper disposal. The study was developed to evaluate the growth of Eucalyptus grandis seedlings submitted to different types and combinations of urban and agro-industrial organic substrates. The experiment was conducted in a greenhouse in a completely randomized design with 10 treatments consisting of different substrates and proportions combinations of them (100% organic compost urban waste (COLU), 100% organic compost of the agro-industrial residue (CORA); 100% commercial substrate; 25% (COLU)+ 75% Commercial; 25% CORA +75% Commercial; 25% COLU + 75% soil; 50% COLU +50% Commercial; 50% CORA +50% Commercial; 50% Commercial + 50% soiland 100% Soil) and 12 repetitions. It was evaluated plant height, stem diameter, number of leaves, length between node, fresh weight of shoot and root dry mass of shoots and roots, total dry weight, main root length, root system length, root volume, average root radius, specific surface area of the root system and stability of clod.The substrates containing organic compost urban show great potential for use as alternative substrates for the production of seedlings of Eucalyptus grandis. A mixture of commercial substrate to organic compost allows the urban growth of root and the shoot of seedlings of Eucalyptus grandis. A mixture of 50% commercial substrate and 50% organic compound of agro-industrial waste provide more stem diameter growth compared to treatments containing soil or over the organic compound of agro-industrial waste.